Bevacizumab Shows Activity in Patients With Low-Grade Serous Ovarian and Primary Peritoneal Cancer. Issue 6 (1st July 2014) - Grisham, Rachel N.; Iyer, Gopa; Sala, Evis; Zhou, Qin; Iasonos, Alexia; DeLair, Deborah; Hyman, David M.; Aghajanian, Carol
Abstract : Objective: Low-grade serous (LGS) ovarian and primary peritoneal cancer is a rare disease with limited therapeutic options. Low response rates are observed with cytotoxic chemotherapy. However, significant responses have been reported in patients treated with bevacizumab. The objective of this study was to determine the response rate to bevacizumab with or without concurrent chemotherapy in patients with recurrent serous borderline or LGS ovarian or primary peritoneal cancer. Methods: This single-institution retrospective study examined the response rate to treatment with bevacizumab in patients with serous borderline or LGS cancer. Patients were treated at the Memorial Sloan Kettering Cancer Center between 2005 and 2012. The best overall response was determined with the use of the Response Evaluation Criteria in Solid Tumors. Results: A total of 17 patients were identified, 15 of whom were evaluable for the primary end point of best overall response. Two patients were treated with bevacizumab as a single agent, and the remainder received bevacizumab in conjunction with chemotherapy (paclitaxel, topotecan, oral cyclophosphamide, gemcitabine, or gemcitabine and carboplatin). The median duration of bevacizumab administration in evaluable patients was 23 weeks (mean, 32.2 weeks; range, 6–79.4 weeks). There were no complete responses. Partial responses were observed in 6 patients (5 patients received concurrent paclitaxel, and 1 patient received concurrent gemcitabine). The overall response rate was 40%, with a response rate of 55% among the subgroup of patients with LGS cancer. Conclusions: These results indicate that bevacizumab in combination with chemotherapy is an active treatment for recurrent LGS ovarian cancer. A prospective trial of bevacizumab in combination with paclitaxel for the treatment of LGS ovarian cancer should be considered.